The Search for the Solution of Personnel Problems of Municipal Service in the Russian Federation - V V Kushnir (RUDN Journal of Political Science, 2013)
The article is devoted to the analysis of a current state of personnel base of municipal service in Russia. The circle of the main problems is outlined, a number of effective technologies and the options promoting their permission are offered. The separate attention is paid to a question of formation of a personnel reserve of the young specialists who have ended higher educational institutions, a technique of selection of highly skilled employees.